2011
DOI: 10.1017/s1352465810000925
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Expressions, Imagery and Perfectionism

Abstract: This research provides an initial exploration of the specific behaviours and intrusive mental imagery associated with perfectionism. The new behavioural measure of perfectionism could prove useful clinically in the assessment of change; however, these findings are preliminary and warrant replication in a clinical sample in order to examine their treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
14
0
3
Order By: Relevance
“…Second, all three forms of perfectionism-self-oriented, otheroriented, and socially prescribed perfectionism-showed unique positive relationships with grandiose fantasy, suggesting all three are associated with compensatory fantasies of being successful and gaining recognition and admiration. Lee, Roberts-Collins, Coughtrey, Phillips, and Shafran (2011) found that perfectionists are prone to intrusive mental images (e.g., intrusive images of problems at work or at school), and our study extends this work by suggesting grandiose mental images are important to perfectionists. For some, perfection may be easier to imagine than to obtain.…”
Section: The Present Findingssupporting
confidence: 82%
“…Second, all three forms of perfectionism-self-oriented, otheroriented, and socially prescribed perfectionism-showed unique positive relationships with grandiose fantasy, suggesting all three are associated with compensatory fantasies of being successful and gaining recognition and admiration. Lee, Roberts-Collins, Coughtrey, Phillips, and Shafran (2011) found that perfectionists are prone to intrusive mental images (e.g., intrusive images of problems at work or at school), and our study extends this work by suggesting grandiose mental images are important to perfectionists. For some, perfection may be easier to imagine than to obtain.…”
Section: The Present Findingssupporting
confidence: 82%
“…In each of these cases, higher overall or subscale scores (particularly the self-critical facet of self-talk) would be expected to be associated with increased self-talk frequency. For example, research shows that perfectionism is associated with increased levels of stress and stress reactivity (Flett et al., 2016) as well as increased intrusive imagery and difficulty completing tasks (Lee et al., 2011). Such tendencies should increase the need for self-regulatory self-talk.…”
Section: The Cognitive Disruption Hypothesismentioning
confidence: 99%
“…On average the interview took 30 minutes to complete. Interviews were transcribed verbatim and data were explored using thematic analysis with descriptive statistics (Smith, 2003), following the approach of Speckens et al (2007), Lee, Roberts-Collins, Coughtrey, Phillips and Shafran (2011) and Philips (2011). Individual sections of material were coded, from which broader themes were derived.…”
Section: Methodsmentioning
confidence: 99%
“…The content and wording of the interview was based on previous studies that have assessed imagery in clinical populations (e.g. Holmes, Crane, Fennell and Williams, 2007; Lee et al, 2011; Osman, Cooper, Hackmann and Veale, 2004; Philips, 2011). The terminology “pictures in your mind” rather than “imagery” was used following the recommendation of Philips (2011).…”
Section: Methodsmentioning
confidence: 99%